2018
DOI: 10.1152/ajplung.00163.2018
|View full text |Cite
|
Sign up to set email alerts
|

ACE-2/ANG1-7 ameliorates ER stress-induced apoptosis in seawater aspiration-induced acute lung injury

Abstract: Previous studies have shown that apoptosis of alveolar cells can be regulated by autocrine of angiotensin (ANG)II and its counter regulatory ACE-2/ANG1-7 axis. Our earlier study has shown that endoplasmic reticulum (ER) stress in response to seawater aspiration eventually led to apoptosis in lung tissue. In this study, we examined the hypothesis that ER stress-induced apoptosis in seawater aspiration-induced acute lung injury (ALI) might also be regulated by the ANGII/ANG1-7 system. ER stress was induced by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…Studies have indicated that COVID-19 acts on the ACE II receptor [ 2 ], which is mainly distributed on type II alveolar epithelial cells regulating lung compliance [ 23 ], but few are distributed on type I alveolar epithelial cells [ 24 ]. COVID-19 pneumonia can lead to dyspnea and chest tightness, even respiratory failure, so patients need high-flow oxygen support, even ventilator therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that COVID-19 acts on the ACE II receptor [ 2 ], which is mainly distributed on type II alveolar epithelial cells regulating lung compliance [ 23 ], but few are distributed on type I alveolar epithelial cells [ 24 ]. COVID-19 pneumonia can lead to dyspnea and chest tightness, even respiratory failure, so patients need high-flow oxygen support, even ventilator therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that ACE2-mediated signaling reduces the effects of ER stress (Zhang et al, 2018). Stimulation of ACE2 by the ligands angiotensin 1-7 suppresses apoptosis mediated by ER stress in alveolar epithelial cells with accumulation of mutant surfactant protein C (Uhal et al, 2013).…”
Section: Sars-cov Sars-cov-2 and Er Stressmentioning
confidence: 99%
“…The mechanisms of the beneficial effects on outcomes in these models include inhibition of apoptosis in AECs and pulmonary microvascular endothelial cells (PVMECs), as well as a reduction in the proliferation and migration of lung fibroblasts. For instance, studies by Ang-(1-7)/MasR enhances survival of AECs, which normally show excessive apoptosis in ARDS [63,64]. Gopallawa and colleagues found that Ang-(1-7)/MasR enhanced mitogen-activated protein kinase phosphatase-2 (MKP-2) which drives apoptosis of AECs [65].…”
Section: Downstream Effects Of the Ace2/ang-(1-7)/masr Axis In Vili Amentioning
confidence: 99%